Development of Injectable Amniotic Membrane Matrix for Postmyocardial Infarction Tissue Repair. Issue 2 (28th November 2019) - Henry, Jeffrey J. D.; Delrosario, Lawrence; Fang, Jun; Wong, Sze Yue; Fang, Qizhi; Sievers, Richard; Kotha, Surya; Wang, Aijun; Farmer, Diana; Janaswamy, Praneeth; Lee, Randall J.; Li, Song
Abstract: Ischemic heart disease represents the leading cause of death worldwide. Heart failure following myocardial infarction (MI) is associated with severe fibrosis formation and cardiac remodeling. Recently, injectable hydrogels have emerged as a promising approach to repair the infarcted heart and improve heart function through minimally invasive administration. Here, a novel injectable human amniotic membrane (hAM) matrix is developed to enhance cardiac regeneration following MI. Human amniotic membrane is isolated from human placenta and engineered to be a thermoresponsive, injectable gel around body temperature. Ultrasound‐guided injection of hAM matrix into rat MI hearts significantly improves cardiac contractility, as measured by ejection fraction (EF), and decrease fibrosis. The results of this study demonstrate the feasibility of engineering as an injectable hAM matrix and its efficacy in attenuating degenerative changes in cardiac function following MI, which may have broad applications in tissue regeneration. Abstract : Injectable hydrogels have emerged as a promising and attractive therapeutic strategy to halt progressive cardiac dysfunction following myocardial infarction (MI), through minimally invasive and localized administration. This study demonstrates that human placental tissue can be decellularized and engineered as the injectable thermoresponsive bioactive gel to significantly promote cardiac regeneration in a rat MI model.